THE FUNCTION OF GRAMMATICAL METAPHOR OF MOOD IN THE CONVERSATION OF BIBLE - Rica Sri Devi Sitorus; Eddy Setia; Dian Marisha Putri (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
AbstractGrammatical metaphor is the transference in the expression of meanings from a congruent representation to another incongruent realization which involves changes in the level of clauses, groups/phrases, words and morphemes. Grammatical metaphor of mood could be found in a conversation by making an identification of speech function based on the utterances whether it was statement, question, command or offer. SFL which is proposed by Halliday (1994) became the theory that would be used to analyzed the function of mood in the conversation between God and Moses regarded with Interpersonal Function. This research aimed to examine about the types of grammatical metaphor of mood and the way it was realized in the conversation between God and Moses. This research applied qualitative descriptive approach. The conversation was taken from Bible because Bible is one of the book that have a great contribution from language side which would not change from age to age. The data would be taken from the conversation between God and Moses at Horeb The Mountain of God in the form of clause and phrase. The source of data in this research is the Holy Bible Exodus 3-19 NIV (New International Version) which is published by Zondervan. Keywords: Grammatical Metaphor, Mood, Speech Function, Coding, Conversation